Research on Financing Mechanism of Long-Term Care Insurance in Xiamen, China: A System Dynamics Simulation - Zhang, Liangwen; Fu, Sijia; Fang, Ya (Frontiers in Public Health, 2021)
Objective: This study aims to predict the changing trend of long-term care insurance (LTCI) funds by clarifying the linkage between the revenue and expenditure and its influencing factors, to provide evidence for the establishment of a sustainable LTCI financing mechanism in China. Method: We take Xiamen as an example, based on the data from Xiamen Special Economic Zone Yearbook and field survey. Based on the System Dynamics model (SDM) of the LTCI financing system, the changing trend of LTCI funds is predicted from 2020 to 2030. Also, through literature research and expert consultation, we found the intervention goals and analyzed their impact on the balance of LTCI funds. Results: According to the forecast, the revenue and expenditure of the LTCI funds will increase year by year from 2020 to 2030 in Xiamen, an increase of about 3.7 times and 8.8 times respectively. After 2029, the expenditure will exceed the revenue of the LTCI funds and the balance will turn into a deficit. With the increase of individual payment rate, government financial subsidies, and unit contribution rate, the revenue of LTCI funds will be increased, and the balance will not face a deficit within the simulation period. However, with the increase of the reimbursement ratio, and severe disability rate, the expenditure of funds will increase, and the balance will turn into a deficit 7 years in advance. In addition, it is found that the severe disability rate has the greatest impact on the balance of funds. Discussion: The SDM can objectively reflect the structure and behavior of the LTCI financing system and has good applicability. By increasing the individual payment rate, government financial subsidies, and unit contribution rate, reasonable setting of the reimbursement ratio, especially the prevention of the elderly disability, in order to maintain the sustainability of the funds. This study provides strong evidence for policymakers to the establishment of a sustainable LTCI system in China.